2002
DOI: 10.1074/jbc.m106479200
|View full text |Cite
|
Sign up to set email alerts
|

Domain Structure of Chondroitin Sulfate E Octasaccharides Binding to Type V Collagen

Abstract: We demonstrated previously that chondroitin sulfate E (ChS-E) binds to type V collagen (Munakata, H., Takagaki, K., Majima, M., and Endo, M. (1999) Glycobiology 9, 1023-1027). In this study, we investigated the structure and binding of ChS-E oligosaccharides. Eleven oligosaccharides were isolated from ChS-E by gel filtration chromatography and anion-exchange high performance liquid chromatography after hydrolysis with testicular hyaluronidase. Separately, seven oligosaccharides were custom synthesized using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 50 publications
(51 reference statements)
1
33
0
Order By: Relevance
“…CD44 binding to type IV collagen and ␣1(IV)1263-1277 is dependent upon CS (21, 44). CS interaction with collagen requires a minimum oligosaccharide chain length and distinct sulfation pattern (76). Conversely, CS interferes with CD44 binding to HA (34).…”
Section: Discussionmentioning
confidence: 99%
“…CD44 binding to type IV collagen and ␣1(IV)1263-1277 is dependent upon CS (21, 44). CS interaction with collagen requires a minimum oligosaccharide chain length and distinct sulfation pattern (76). Conversely, CS interferes with CD44 binding to HA (34).…”
Section: Discussionmentioning
confidence: 99%
“…CSE binds to collagen type ll, V and Vlll, whereas heparin binds to collagen type V and lX, and other GAGs do not interact with any type of collagen [40]. The domain structure of CSE responsible for binding to type V collagen has been elucidated by Takagaki et al [41]. They found that three consecutive GlcAb1-3GalNAc (4S,6S) units were a prerequisite for the interaction.…”
Section: Discussionmentioning
confidence: 96%
“…Recent remarkable research has revealed some specific biological properties of CS-E, [16][17][18][19][20][21] whereas sufficient amounts of CS-E have not been detected in other animals. In addition, CS composed exclusively of the Etype cannot be obtained naturally.…”
Section: Resultsmentioning
confidence: 99%